تأثير إستخدام تدريبات الساکيو( S.A.Q ) علي مستوي اداء الرشاقة الخاصة لدي ناشئي الکرة الطائرة The effect of using Sakyo exercises (S.A.Q) on the level of performance of special agility among volleyball juniors - أمنية أيمن فتحى السيد (Beni-Suef University, Faculty of Physical Education, 2022)
أجريت الدراسة بهدف إستخدام تدريبات الساکيو (S.A.Q) لمعرفة تأثيرها على مستوى اداء الرشاقة الخاصة لدى ناشئي الکرة الطائرة ( تحت 17 سنة ), کما تم افتراض انه توجد فروق ذات دلاله احصائيه بين متوسطى القياسين القبلي والبعدي للمجموعة التجريبية فى مستوى اداء الرشاقة الخاصة لصالح القياس البعدي , و تم اختيار عينة البحث بالطريقة العمدية من ناشئى الکرة الطائرة تحت 17 سنة بنادى المحافظة والمقيدين بالاتحاد المصرى للکرة الطائرة بالفيوم والبالغ عددهم 16 لاعب وتوصلت النتائج الى ان إستخدام تدريبات الساکيو ( S.A.Q) يؤثر تأثيرا إيجابيا علي الرشاقة الخاصة لناشئى الکرة الطائرة . The study was conducted with the aim of using SAQ training to find out its effect on the level of special agility performance of volleyball juniors (under 17 years old), as it was assumed that there are statistically significant differences between the mean of the pre and post measurements of the experimental group in the level of special agility performance in favor of the post measurement. The research sample was chosen in a deliberate way from 16 players of volleyball juniors under 17 years old in the Governorate Club and those enrolled in the Egyptian Volleyball Federation in Fayoum. The results concluded that the use of SAQ exercises positively affects the special agility of volleyball juniors.